Investigation of cullin-3 gene expression changes in people with colorectal cancer and polyps in China: Cullin-3 gene expression in colorectal cancer and polyps - Wei, Xiaoguo; Zhao, Xin; Zhao, Xinyan; Yang, Xiaoxiong (Cellular and Molecular Biology, 2023)
Colorectal cancer (CRC) is one of the most common fatal malignancies caused by environmental and genetic factors. Considering the increasing frequency of CRC worldwide, especially in China, the importance of research on CRC is more widely defined. A recent study focused on molecular pathways involved in colon cancer carcinogenesis to improve cancer diagnosis and treatment to identify new biomarkers. Colon cancer is the result of dysplasia in primary growths of the intestine, known as polyps. These early growths are unknown and different in terms of morphology, molecular mechanisms, and the ability to cause colon cancer. This study aims to investigate the expression level of the CUL3 gene in polyps and colorectal cancer. This cross-sectional study collected 300 colorectal tissue biopsy samples, including 40 tumor tissue samples, 73 precancerous lesions with their adjacent tissue, and 31 normal tissue samples. The expression of the CUL3 gene was investigated by the Real-time PCR method. There was no significant difference in CUL3 mRNA expression between polyp tissues and their adjacent samples (p = 0.41). Our results showed no statistically significant difference in CUL3 gene expression between tumor tissues and their adjacent thermal samples (p = 0.78) and between tumor and polyp groups (p = 0.53). CUL3 may play an essential role in regulating cancer and CRC progression by stimulating the proteasomal degradation of various tumor suppressors or oncogenes. Studies on the effective substrates of CUL3 in colorectal cancer are essential.